Drainage Channels to Control Flooding and Road Damage - Alik Ansyori Alamsyah (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2020)
The purpose of this program is to motivate the community to build and control the drainage channels. Ngenep Village often experiences floods caused by high rainfall and extreme differences in the original land surface. Seeing this condition, an assistance program should be carried out to realize the hopes of the people of Ngenep Village to have a drainage channel that can hold rainwater. This program is carried out on the residents of Ngenep Village, Karangploso Malang with the hope of increasing the accessibility of the Ngenep village community and other villages that often pass the road. This program was carried out with data collection and data processing that included observations and interviews with the people of Ngenep Village. It was found that the people of Ngenep Village lacked awareness of their environment and cleanliness, this was compounded by the lack of role of the Village apparatus as Modeling or who gave treatments that could set an example for the Ngenep Village Community. The results of the intervention, especially training and outreach to citizens, showed an increase in motivation to change lifestyles from the inattentive to be more attentive to the environment, this is indicated by the start to maintenance drainage channels.